RELIGIOUS SOLIDARITY VS. PRODUCT UTILITY: THE MODERATING ROLE OF ISLAMIC BRANDING ON CONSUMER BOYCOTT INTENTIONS IN THE WORLD'S LARGEST MUSLIM POPULATION - Ichsan; Damanhur; Nurjanius Situmorang; Hanif; T.Saifullah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
In the largest Muslim market globally, consumers encounter a multifaceted psychological conflict between the imperatives of religious solidarity and the pragmatic dependence on the functional utility of global products, resulting in a systemic ambiguity regarding boycott intentions that remains inadequately examined in the Islamic marketing literature. This study seeks to provide a comprehensive conceptual model that elucidates the impact of religious solidarity and product utility on the boycott intentions of Indonesian Muslim customers, with Islamic branding serving as a moderating variable. This study used a Framework Synthesis-based integrative conceptual examination of esteemed literature from 2010 to 2026 to amalgamate Social Identity Theory with the Consumer Animosity Model, resulting in three empirically tested theoretical assertions. Conceptual findings suggest that religious solidarity enhances boycott intentions, whereas product utility diminishes them via the mechanism of constrained rationality. Authentic Islamic branding significantly enhances the impact of religious unity without diminishing the supremacy of functional utility by incorporating the spiritual utility aspect into consumers' overall value assessment. The findings suggest that domestic marketers must establish genuine Islamic brand equity, but global corporations should emphasize cultural sensitivity as a means to reduce reputational risk in modern Muslim markets.